Math, asked by ramesh9603547, 1 year ago

(m-n) ³+(n-r) ³+(r-m) ³/6(m-n) (n-r) (r-m) =

Answers

Answered by MaheswariS
4

Answer:

\bf\frac{(m-n)^3+(n-r)^3+(r-m)^3}{6(m-n)(n-r)(r-m)}=\frac{1}{2}

Step-by-step explanation:

\textbf{Given:}

\displaystyle\frac{(m-n)^3+(n-r)^3+(r-m)^3}{6(m-n)(n-r)(r-m)}

\text{we know that,}

\text{If $\bf\,a+b+c=0$, then $\bf\,a^3+b^3+c^3=3abc$}

\text{Here, $(m-n)+(n-r)+(r-m)=0$}

\implies(m-n)^3+(n-r)^3+(r-m)^3=3(m-n)(n-r)(r-m)

\text{Now,}

\displaystyle\frac{(m-n)^3+(n-r)^3+(r-m)^3}{6(m-n)(n-r)(r-m)}

=\displaystyle\frac{3(m-n)(n-r)(r-m)}{6(m-n)(n-r)(r-m)}

=\frac{3}{6}

=\frac{1}{2}

\implies\boxed{\bf\frac{(m-n)^3+(n-r)^3+(r-m)^3}{6(m-n)(n-r)(r-m)}=\frac{1}{2}}

Answered by guptasingh4564
0

So, The answer is 1

Step-by-step explanation:

Given,

\frac{(m-n)^{3}+(n-r)^{3}+(r-m)^{3}   }{6(m-n)(n-r)(r-n)} =?

We know,

a^{3}+b^{3}+c^{3}-3abc=0 if (a+b+c)=0

a^{3}+b^{3}+c^{3}=3abc

Here,

(m-n)+(n-r)+(r-m)=0

Then,

(m-n)^3+(n-r)^3+(r-m)^3=3(m-n)(n-r)(r-m)

\frac{(m-n)^{3}+(n-r)^{3}+(r-m)^{3}   }{3(m-n)(n-r)(r-n)} =1

\frac{(m-n)^{3}+(n-r)^{3}+(r-m)^{3}   }{6(m-n)(n-r)(r-n)} =\frac{1}{2}  (by multiplying \frac{1}{2} on both sides )

∴ The answer is 1

Similar questions